THE ROLE OF THE TEACHER AS A FACILITATOR IN COMMUNITY LANGUAGE LEARNING - Shahina Shukhratova (Web of Journals Publishing, 2025)
Community Language Learning (CLL) is an innovative pedagogical approach that prioritizes the creation of a supportive and collaborative learning environment, where the teacher assumes the role of a facilitator rather than a traditional instructor. This article delves into the methodological aspects of the teacher's role in CLL, emphasizing the importance of building trust, fostering peer interaction, and promoting learner autonomy. Through a comprehensive literature review and practical analysis, this study highlights how effective facilitation can significantly enhance language acquisition and learner engagement within community-based language learning settings. The findings underscore the transformative potential of the facilitator's role in cultivating a positive learning atmosphere that encourages active participation and personal growth among learners.
Keywords: Community Language Learning, teacher as facilitator, language acquisition, peer interaction, learner autonomy.